Determination of influenza B identity and potency in quadrivalent inactivated influenza vaccines using lineage-specific monoclonal antibodies. - Swati Verma; Jackeline Soto; Anupama Vasudevan; Falko Schmeisser; Esmeralda Alvarado-Facundo; Wei Wang; Carol D Weiss; Jerry P Weir (PLoS ONE, 2017)
Co-circulation of two antigenically and genetically distinct lineages of influenza B virus, represented by prototype viruses B/Victoria/2/1987 and B/Yamagata/16/1988, has led to the development of quadrivalent influenza vaccines that contain two influenza B antigens. The inclusion of two influenza B antigens presents challenges for the production and regulation of inactivated quadrivalent vaccines, including the potential for cross-reactivity of the reagents used in identity and potency assays because of the relative close relatedness of the hemagglutinin (HA) from the two virus lineages. Monoclonal antibodies (mAbs) specific for the two lineages of influenza B HA were generated and characterized and used to set-up simple identity tests that distinguish the influenza B antigens in inactivated trivalent and quadrivalent vaccines. The lineage-specific mAbs bound well to the HA of influenza B strains included in influenza vaccines over a period of more than 10 years, suggesting that identity tests using such lineage-specific mAbs would not necessarily have to be updated with every influenza B vaccine strain change. These lineage-specific mAbs were also used in an antibody capture ELISA format to quantify HA in vaccine samples, including monovalent, trivalent, and quadrivalent vaccine samples from various manufacturers. The results demonstrated correlation with HA values determined by the traditional single radial immunodiffusion (SRID) assay. Further, the antibody-capture ELISA was able to distinguish heat-stressed vaccine from unstressed vaccine, and was similar to the SRID in quantifying the resultant loss of potency. These mAb reagents should be useful for further development of antibody-based alternative influenza B identity and potency assays.